Financial Decision-Making of Female Culinary MSME Entrepreneurs in Gorontalo City: Integrating Digital Financial Literacy, Financial Capability, and Spending Behavior within Financial Behavior Theory - Musafir Musafir; Eka Zahra Solikahan; Ariawan Ariawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The article examines the financial decision-making processes of female entrepreneurs in the culinary sector of micro, small, and medium enterprises (MSMEs) in Gorontalo City, Indonesia, drawing on financial behavior theory. It highlights the critical role of MSMEs in the national economy, particularly the dominance of women in the culinary subsector, while identifying key challenges such as limited digital financial literacy, financial capability, and uncontrolled spending behavior. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 software, the study analyzes data from 120 purposively sampled female entrepreneurs aged 20–50 years. The findings reveal that digital financial literacy significantly influences both financial capability and spending behavior, but it does not directly affect financial decision making. In contrast, financial capability and spending behavior exert strong positive and significant effects on financial decision making, with financial capability showing the strongest impact. The model demonstrates good fit (SRMR < 0.10), and measurement validity and reliability are adequately established after removing invalid indicators. The discussion attributes the non-significant direct link between digital financial literacy and decision making to the continued reliance on traditional business experience and hybrid practices among respondents. Overall, the study contributes theoretically by reinforcing a gender-sensitive financial decision-making framework and practically by offering insights for empowerment programs focused on enhancing digital financial literacy and financial management skills among female MSME owners.